2018
DOI: 10.3324/haematol.2018.193615
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes and management strategies for venetoclax-treated chronic lymphocytic leukemia patients in the United States

Abstract: Venetoclax is a BCL2 inhibitor approved for 17p-deleted relapsed/refractory chronic lymphocytic leukemia with activity following kinase inhibitors. We conducted a multicenter retrospective cohort analysis of patients with chronic lymphocytic leukemia treated with venetoclax to describe outcomes, toxicities, and treatment selection following venetoclax discontinuation. A total of 141 chronic lymphocytic leukemia patients were included (98% relapsed/refractory). Median age at venetoclax initiation was 67 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
136
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 17 publications
13
136
2
4
Order By: Relevance
“…Our data provide the first evidence in the non‐trial setting of equivalent efficacy and survival in patients exposed to BTKi, PI3Ki or both classes of BCRi. Notably, and by contrast to recently published US RWD (Mato et al , 2018b), we did not find significant differences in response or survival outcomes according to TP53 status. Consistent with a pooled analysis of 3 clinical trials of venetoclax monotherapy (Wierda et al , 2017b), we demonstrate that more heavily pre‐treated patients had an inferior PFS, although significance was not retained as an independent predictive factor in a multivariable analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data provide the first evidence in the non‐trial setting of equivalent efficacy and survival in patients exposed to BTKi, PI3Ki or both classes of BCRi. Notably, and by contrast to recently published US RWD (Mato et al , 2018b), we did not find significant differences in response or survival outcomes according to TP53 status. Consistent with a pooled analysis of 3 clinical trials of venetoclax monotherapy (Wierda et al , 2017b), we demonstrate that more heavily pre‐treated patients had an inferior PFS, although significance was not retained as an independent predictive factor in a multivariable analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast to published non‐clinical trial BCRi data, where toxicity was the most common reason for BCRi discontinuation (followed by CLL PD (Mato et al , 2018a)), PD was the commonest reason for venetoclax discontinuation. These data are strikingly similar to results reported by Mato et al (2018b) (22/45 PD [CLL and RT] and 7/45 toxicity in the present UK series; 22/41 PD [CLL and RT] and 9/41 toxicity in the US series).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recent large retrospective, multicentre series (Mato et al, ; Eyre et al, ) have demonstrated reassuringly similar efficacy and survival to trial outcomes. A toxicity analysis [including rates of tumour lysis syndrome (TLS), dose interruptions and discontinuations] has been assessed in a recent all‐age cohort (Roeker et al, ) but the specific question of efficacy and tolerability in elderly non‐trial patients has not been specifically addressed.…”
Section: Treatment Complications Comparing Age Categoriesmentioning
confidence: 91%
“…Also, given the potency of venetoclax, with its ability to cause TLS, it is perhaps surprising and very reassuring that real‐world clinicians are able to replicate the response rates and clinical benefits achieved in clinical trials using an agent which many would regard as less than easy to deliver. A similar real‐world study from the USA revealed a rather disappointing ORR of 72% but follow‐up was very short at only 7 months and results may improve (Mato et al , ). Also, 29% of patients stopped the venetoclax therapy in the USA study (Mato et al , ) compared to only 8% in the study reported by Eyre et al ().…”
mentioning
confidence: 99%